Factores que determinan la cultura exportadora en los artesanos de la ciudad de Iquitos 2023 - Salas Ramos, Lucero del Pilar (2024)
The objective of this thesis report was to identify the factors that determine the export culture in the artisans of the City of Iquitos 2023, in which an applied type study was used, explanatory level with a non-experimental design, taking 157 artisans as a sample. to whom a questionnaire was used to collect information. The results showed: it was decisive that the variables production process (p=0.022), suppliers (p=0.001), target market (p=0.014) and financial resources (p=0.000) play a significant role in predicting culture. exporter. Specifically, the production process explains 40.4% of the variable. Furthermore, coordination with suppliers explains 46.2% of the variable. Along the same lines, the identification of the target market explains 45.8% of the variable. Also, the management of financial resources explains 46.6% of the variable. Similarly, human resources management explains 41.2% of the variable. It was determined that the identification of competitors explains 38.7% of the variable. Finally, it was determined that the export process explains 41.2% of the variable. All of them have demonstrated significant influence at the 0.000 level.